2007
DOI: 10.1002/jnr.21267
|View full text |Cite
|
Sign up to set email alerts
|

Swedish amyloid precursor protein mutation increases phosphorylation of eIF2α in vitro and in vivo

Abstract: Swedish double mutation (KM670/671NL) of amyloid precursor protein (Swe‐APP), a prevailing cause of familial Alzheimer's disease (FAD), is known to increase in Aβ production both in vitro and in vivo, but its underlying molecular basis leading to Alzheimer's disease (AD) pathogenesis remains to be elucidated, especially for the early phase of disease. We have confirmed initially that the expression of Swe‐APP mutant transgene reduced cell viability via ROS production but this effect was eliminated by an anti‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
(52 reference statements)
7
33
0
Order By: Relevance
“…In agreement with previous findings, we found that phosphorylation of eIF2a was significantly increased in the hippocampi of 12-to 16-month-old Tg2576 mice compared to age-matched non-transgenic mice (Figs. 4B,E, P < 0.001 vs. saline treated Tg2576 mice; Kim et al, 2007). Treatment with PBA completely suppressed eIF2a phosphorylation in Tg2576 mice, indicating relief of ER stress ( Fig.…”
Section: Effects Of Pba On Intraneuronal Ab and Er Stress Responsesmentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement with previous findings, we found that phosphorylation of eIF2a was significantly increased in the hippocampi of 12-to 16-month-old Tg2576 mice compared to age-matched non-transgenic mice (Figs. 4B,E, P < 0.001 vs. saline treated Tg2576 mice; Kim et al, 2007). Treatment with PBA completely suppressed eIF2a phosphorylation in Tg2576 mice, indicating relief of ER stress ( Fig.…”
Section: Effects Of Pba On Intraneuronal Ab and Er Stress Responsesmentioning
confidence: 86%
“…Decreased Ab accumulation and GRP78 upregulation was associated with a normalization of the levels of phosphorylated eIF2a, an indicator of ER stress which shuts down protein synthesis and is increased in brains of AD animal models and AD patients (Chang et al, 2002;Kim et al, 2007). Altered eIF2a phosphorylation may decrease the efficacy of mRNA translation and de novo protein synthesis which are required for plasticity and normalization of this parameter might contribute to the improvement in learning and memory conferred by PBA.…”
Section: Effects Of Pba On Ab Clearancementioning
confidence: 86%
“…In addition, increased eIF2a phosphoryation in the brain is associated with epilepsy (Carnevalli et al 2006) and neuronal culture models of Parkinson's disease (PD) (Holtz and O'Malley 2003). Moreover, eIF2a phosphorylation increases in the hippocampus of mouse models of Alzheimer's disease (Page et al 2006;Kim et al 2007), as well as brains of AD patients (Kim et al 2007). Mutations in phosphatase and tensin homolog on chromosome ten (PTEN), a tumor suppressor gene involved in upstream regulation of Akt and mTOR signaling, have been reported in autistic individuals with macrocephaly (Butler et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A link between Alzheimer’s disease (AD) and reduced global translation was established in 1989, when Langstrom et al demonstrated that polysomes from the cortices of AD patients were associated with less RNA than those from controls. Subsequently, increased levels of p-eIF2α were found in the cortex and hippocampus of AD patients and in AD mouse models (Chang et al, 2002b; Devi and Ohno, 2013; Hoozemans et al, 2009; Kim et al, 2007; Lewerenz and Maher, 2009; Ma et al, 2013; Mouton-Liger et al, 2012; O’Connor et al, 2008; Page et al, 2006; Stutzbach et al, 2013; Unterberger et al, 2006). In addition to AD, p-eIF2α levels are elevated in the brain or spinal cord of patients and mice with prion disease (Unterberger et al, 2006), amyotrophic lateral sclerosis (ALS; Ilieva et al, 2007), Parkinson’s disease (PD; Hoozemans et al, 2007, 2012), Huntington’s disease (HD; Leitman et al, 2014), and various tauopathies (Köhler et al, 2014; Nijholt et al, 2012; Radford et al, 2015; Stutzbach et al, 2013; Unterberger et al, 2006).…”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 99%